Cross sectional analyses on the prevalence and usage of braille among blind children - Kumaresan, Vinisha; Prem, Astha; Anuradha, P. (International Journal of Research in Medical Sciences, 2022)
Background: Childhood blindness is a serious issue which has to be dealt with importance because the disability adjusted life years (DALY) loss in a blind child is much more than that of adults with blindness. The ability to read and write in any one language improves their confidence and makes them more independent. It gives them hope not just to live but also to make a living. This study was done to emphasize on the importance of braille. This study analyses the prevalence and utilization of braille among blind children and its impact on education and overall quality of life. Methods: The data required was collected from the ophthalmology outpatient department (OPD), Saveetha Medical College and Hospital, Thandalam. The children were asked to answer questions based on a questionnaire after taking informed consent from them and their parents. Results: According to the data collected from 50 blind children over 6 months, only 12% used only braille for their educational purposes, 58% used only other assistive technologies, and 30% used both braille and other assistive technologies. Conclusions: This study shows that there is more inclination towards using assistive technology than Braille for education and practical purpose as it is easy to learn. But it is important that the government encourages schools to teach Braille to all students and also incorporate Braille in the public forum as its advantages are many which cannot be replaced by other assistive technologies.